2017
DOI: 10.1002/cam4.1219
|View full text |Cite
|
Sign up to set email alerts
|

Identifying patterns of adaptation in breast cancer patients with cancer‐related fatigue using response shift analyses at subgroup level

Abstract: Fatigue is the most prevalent symptom in breast cancer. It might be perceived differently among patients over time as a consequence of the differing patients’ adaptation and psychological adjustment to their cancer experience which can be related to response shift (RS). RS analyses can provide important insights on patients’ adaptation to cancer but it is usually assumed that RS occurs in the same way in all individuals which is unrealistic. This study aimed to identify patients’ subgroups in which different R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 35 publications
1
30
0
2
Order By: Relevance
“…Our findings are in line with previous studies that reported that fatigue was a persistent problem among women with breast cancer [12,16,32,33]. However, the recruitment procedures were not comparable, since we included women before diagnosis, while others included women after diagnosis and in some studies much later [16].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our findings are in line with previous studies that reported that fatigue was a persistent problem among women with breast cancer [12,16,32,33]. However, the recruitment procedures were not comparable, since we included women before diagnosis, while others included women after diagnosis and in some studies much later [16].…”
Section: Discussionsupporting
confidence: 90%
“…Only few previous studies applied repeated measurements, for example a study of breast cancer patients treated with radiotherapy, who were completing the Lee Fatigue Scale every 2 weeks for 2 months, and once a month for 2 months during and following radiotherapy [34]. Another study measured fatigue and other health related quality of life measures before diagnosis, 3 months after initial treatment and 1 year after completion of treatment, and found that elevated levels of fatigue was persistent 18 months after initial treatment [35], while a recent study measured fatigue before treatment and after four and 8 months [32], a study from Taiwan measured fatigue 9 times during the first year after treatment [36] and finally a recent French study with 10 measurement with MFI-20 during 2 years after diagnosis [12]. The latter study does not compare to women without cancer and starts follow-up after diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations